Alzheimer’s Disease-Related Cerebrospinal Fluid Biomarkers in Progressive Supranuclear Palsy - Takanobu Ishiguro; Kensaku Kasuga (Brain Sciences)
Progressive Supranuclear Palsy (PSP) is the most common four-repeat tauopathy. PSP cases are typically characterized by vertical gaze palsy and postural instability; however, various phenotypes have been reported, making antemortem diagnosis based on clinical symptoms challenging. The development of biomarkers reflecting brain pathology and the ability to diagnose patients based on these biomarkers are essential for developing future intervention strategies, including disease-modifying therapies. However, despite many dedicated efforts, no highly specific fluid biomarker for PSP has yet been established. Conversely, several cerebrospinal fluid (CSF) biomarkers of Alzheimer’s Disease (AD) have been established, and an AT(N) classification system has been proposed. Typically, among patients with AD, CSF amyloid β42 (Aβ42), but not Aβ40, is decreased, resulting in a reduction in the Aβ42/Aβ40 ratio, while tau phosphorylated at threonine 181 (p-tau181) and total tau (t-tau) are increased. Interestingly, the core CSF AD biomarkers show unique patterns in patients with PSP. Furthermore, reports have indicated that the CSF levels of both Aβ42 and Aβ40 are decreased independently of Aβ accumulation in PSP. Therefore, the Aβ42/Aβ40 ratio could potentially be used to differentiate PSP from AD. Additionally, studies have reported that CSF p-tau and t-tau are reduced in PSP, and that the neurofilament light chain is remarkably increased compared to healthy controls and patients with AD, even though PSP is a neurodegenerative disease associated with tau accumulation. These PSP-specific changes in AD-related core biomarkers may reflect the pathology of PSP and contribute to its diagnosis. As such, elucidating the mechanisms underlying the observed decreases in Aβ and tau levels could facilitate a better understanding of the pathogenesis of PSP.